ANALISIS AKUNTANSI PENGGAJIAN BERBASIS SISTEM INFORMASI AKUNTANSI PADA MIE DJW DI BLITAR - Fika Umi Azizah; Arif Wahyudi (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya, 2026)
This Study Analyzes The Payroll System Implemented At Mie Djw, A Micro, Small, and Medium Enterprise (Msme), and Examines Its Role In Supporting Transparency and Accountability In Business Management. The Research Uses A Qualitative Approach With A Case Study Method. Data Were Collected Through Direct Observation Of The Payroll Process, Interviews With Management and Employees, and Examination Of Supporting Documents Such As Attendance Records and Payroll Slips. The Results Show That The Payroll System Applies The Basic Elements Of An Accounting Information System, Including Attendance Data As Input, Wage Calculation As The Process, and Salary Payments and Payroll Slips As Output. The Use Of A Fingerprint-Based Attendance System Improves Recording Accuracy, While The Owner’s Involvement In Payroll Validation Strengthens Accountability. The Provision Of Payroll Slips and Informal Clarification Mechanisms Also Supports Transparency. However, The Absence Of Standardized Written Procedures and Formal Documentation Limits The Audit Trail. This Study Demonstrates That A Simple Payroll System Can Function Effectively In An Msme, But Requires Procedural Improvements To Ensure Long-Term Accountability.